Differences Between Premenopausal And Postmenopausal Coronary Artery Disease (CAD) Risk Factors and Clinical Profile - Hossain, Md Shahadat; Bhuiyan, Mohammad Abdus Sattar; Sowdagar, Lt. Col. Mohammad Nizamul Hossain; Siddique, Nure Alam; paul, Gobinda kanti; Paul, Protap Kumar; Shakil, Shiblee Sadeque; Khan, Md. Tariqul Islam; Sohan, Arif Mohammad; Alam, Md.Musaddequl; Hoque , Mohammed Shahidul (International Journal of Medical Research and Review, 2024)
Introduction: Coronary artery disease is the leading cause of mortality and morbidity of both men and women accounting for over one third of total deaths [1]. It has reached epidemic proportion among Indians. It accounts for 1 out of 3 women death regardless of the race or ethnicity [2]. In women, the annual mortality rate from CAD is high. Objective: To assess the differences between premenopausal and postmenopausal coronary artery disease (CAD) risk factors, clinical manifestation, clinical profile and angiographic characteristics. Methods: A prospective observation study was conducted at cardiology department, NICVD, Dhaka, Bangladesh from January to December 2019. Total 200 female CAD patients were drawn from the cardiology department. The subjects were enrolled in accordance with the criterion of diameter stenosis ≥50% in left mean and ≥70% in LAD, LCX and ECA in at least one invasive coronary angiogram. Patients with pulmonary embolism, aortic aneurysm, congenital heart disease, rheumatic heart disease, myocarditis, or cardiomyopathy were excluded. A total of 50 premenopausal cases and 150 postmenopausal cases were enrolled according to their status at the time of diagnosis. All patients underwent percutaneous coronary intervention and were given conventional drug therapy for coronary artery disease during follow-up. Results: Differences were compared between the 2 groups. Fewer premenopausal women suffered from hypertension (46% versus 82%, P< 0.001), type 2 diabetes (10% versus 36%, P = 0.001), and hyperlipidemia (4% versus 36%, P<0.001), but more had a positive family history of premature CAD (42% versus 26%, P = 0.03). Acute coronary syndrome (ACS) was more frequently seen in premenopausal women (80% versus 48%, P < 0.001), and their left anterior descending branch was the vessel most often involved (68%). The cumulative recurrence rate was 1.76 times higher in postmenopausal patients than premenopausal patients. Clinical diagnosis (HR = 2.54, 95%CI: 1.21-4.85, P = 0.02) and type 2 diabetes (HR = 4.10, 95%CI: 2.37-8.83, P = 0.004) were two factors that influenced recurrence in premenopausal subjects, while the clinical diagnosis (HR = 1.93, 95%CI: 1.59-3.46, P = 0.03) and Gensini score (HR =1.20, 95% CI: 1.11-1.45, P = 0.02) were influencing factors in the postmenopausal patients. Symptoms among younger women were atypical, but the onset of disease was faster and more urgent. Conclusion: Our study clarified the differences between postmenopausal and premenopausal women with respect to risk factors, clinical symptoms, cardiovascular features, and recurrence rate, and provided a reference for further study on the mechanism and prognosis in postmenopausal or premenopausal CAD patients.